Taxonomy of international cooperation for development through the process of Central America integration - Tobar, Laura Michelle Godoy; del Pozo, Pedro Caldentey; Cano, Vicente González (Frontiers in Political Science, 2025)
BackgroundThe Central American Integration System (SICA) faces significant financial and institutional challenges despite its crucial role in regional integration. International cooperation has been instrumental in supporting SICA through the provision of essential financial resources and technical assistance.AimThis study aimed to analyze the nature and operational dynamics of international cooperation within SICA. Specifically, it sought to develop a comprehensive taxonomy of cooperation actors and establish a Cooperation Quality Index (CQI) to assess the relevance and efficacy of their contributions to regional integration.MethodsInternational cooperation flows to SICA from 2000–2018 were analyzed through the examination of variables such as volume, thematic focus, modality, and dialogue mechanisms. These variables were refined using the Delphi method with domain experts. A cluster analysis, complemented by the CQI, was then employed to group cooperation actors and construct a contributions-based taxonomy.ResultsThe analysis identified six distinct cooperation clusters, three of which met high-quality standards and account for a substantial proportion of cooperation resources received by SICA. These findings illuminate the critical characteristics international development cooperation must encompass to significantly impact SICA’s functioning and advance regional integration.ConclusionInternational cooperation plays a crucial role in SICA by helping to compensate for its financial and resource limitations. The findings indicate that high-quality cooperation is indispensable for fostering regional integration and achieving sustainable, inclusive development in Central America. This research provides a robust framework for optimizing cooperation strategies and maximizing its transformative potential.